2017
DOI: 10.1002/cbdv.201700444
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Reactivity of Polyclonal Antibodies against Canavalia ensiformis (Jack Bean) Urease and Helicobacter pylori Urease Subunit A Fragments

Abstract: Overlapping decapeptide fragments of H. pylori urease subunit A (UreA) were synthesized and tested with polyclonal antibodies against Canavalia ensiformis (Jack bean) urease. The linear epitopes of UreA identified using the dot blot method were then examined using epitope mapping. For this purpose, series of overlapping fragments of UreA, frameshifted AE four amino acid residues were synthesized. Most of the UreA epitopes which reacted with the Jack bean urease polyclonal antibodies had been recognized in prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The automatic SPOT method with the use of cellulose modified with 1,3,5-triazine derivative [12] was used to synthesize the library of collagen II fragments immobilized on cellulose. The 1,3,5-triazine derivative acts as a linker separating the peptide from the cellulose matrix and ensuring its appropriate exposure to interaction with antibodies [13].…”
Section: Resultsmentioning
confidence: 99%
“…The automatic SPOT method with the use of cellulose modified with 1,3,5-triazine derivative [12] was used to synthesize the library of collagen II fragments immobilized on cellulose. The 1,3,5-triazine derivative acts as a linker separating the peptide from the cellulose matrix and ensuring its appropriate exposure to interaction with antibodies [13].…”
Section: Resultsmentioning
confidence: 99%
“…The libraries of fragments of TGF-α, EGF, and VEGF A were obtained. The first stage of the synthetic work involved the incorporation of the isocyanurate derivative on the surface of the cellulose matrix [30,31] (Figure 1). As our research has shown, the isocyanurate derivatives can be used in the SPOT peptide synthesis (modified cellulose as a solid phase) according to the Fmoc/tBu strategy.…”
Section: Resultsmentioning
confidence: 99%
“…The epitope mapping of cTnI in combination with previous studies, conducted in our lab, resulted in the selection of four peptide sequences which are cTnI [19][20][21][22][23][24][25][26][27][28][29][30][31] , cTnI 66-77 , cTnI 110-122 , cTnI [118][119][120][121][122][123][124][125][126][127][128][129][130][131] . The synthesized conjugates are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The plate was then washed with THF (3 × 10 mL), treated with a solution of Fmoc-Ala-OH (1.556 g, 5 mM) and NMM (0.55 mL, 5 mM) in dichloromethane (DCM, 20 mL) for 4 h, washed with DCM (5 × 10 mL), and then the excess solvent was removed. The plate was immersed in dry boiling toluene for 6 h and then dried thoroughly in a vacuum desiccator (Kaminski et al 2018). The Fmoc group was removed by treatment with a 25% solution of piperidine in dimethyl formamide (DMF, 20 mL) for 15 min followed by washing with DMF (2 × 10 mL) and DCM (2 × 10 mL).…”
Section: Immobilization Of Alanine On the Cellulose Platementioning
confidence: 99%
“…In earlier studies we revealed that Helicobacter pylori Ure A fragments 11-24, 21-33, and 31-42 were able to interact with Jack bean urease antibodies (Kaminski et al 2018).…”
Section: Introductionmentioning
confidence: 96%